Different spray droplet evaporation models for non-ideal multi-component fuels with experimental validation. (March 2016) - Chen, Longfei; Liu, Zhixin; Lin, Yuzhen; Zhang, Chi
Highlights: A correlation between activity coefficient and mole fraction was demonstrated. The activity coefficients was incorporated with the heat and mass transfer models. For butanol blends, three models can simulate the evaporation processes accurately. The well mixed model is suitable for predicting slow evaporation processes. Abstract: Herein three heat and mass transfer models were considered: the well-mixed (WM) model, the frozen evaporation (FZ) model and the diffusion controlled (DC) model for multi-component droplet evaporation were compared and validated against experimental data. The test fuels were mixtures of n-decane (a surrogate fuel for kerosene) and alcohol (ethanol or butanol) with differing volumetric ratios. Since the test fuels are non-ideal solutions, the activity coefficient of each fuel component was calculated by using the UNIFAC method and was incorporated with the heat and mass transfer models to account for the non-linearity effect on fuel evaporation process. Single-camera and PIV (Particle image velocimetry) measurements yielded the velocity distributions of fuel droplets at two cross-sections of the spray cone with different axial distances. The Sauter Mean Diameter (SMD) of spray droplets were measured by a LSA-III Malvern particle size analyzer. For butanol–decane blends, all the three different models can predict the evaporation accurately with little variation. Whilst, prediction of evaporation for ethanol–decane blends suffers much more noticeable variation among the models because of the relatively higher saturation vapor pressure of ethanol. A great deviation between the predicted droplet size and the measured SMD was observed for E10 (10% ethanol by volume) because the activity coefficient of ethanol for E10, and thus the evaporation rate, is more susceptible to the variation of the ethanol mole fraction. The well mixed model can be considered suitable for predicting slow evaporation processes with low injection pressures.